2017
DOI: 10.1160/th16-04-0322
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemia suppresses microRNA expression in platelets to increase P2RY12 and SELP levels in type 2 diabetes mellitus

Abstract: Megakaryocyte (MK)-derived miRNAs have been detected in platelets. Here, we analysed the expression of platelet and circulating miR-223, miR-26b, miR-126 and miR-140 that might be altered with their target mRNAs in type 2 diabetes mellitus (DM2). MiRNAs were isolated from leukocyte-depleted platelets and plasma samples obtained from 28 obese DM2, 19 non-DM obese and 23 healthy individuals. The effect of hyperglycaemia on miRNAs was also evaluated in MKs using MEG-01 and K562 cells under hyperglycaemic conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 51 publications
5
70
0
4
Order By: Relevance
“…DM mice have reduced miR-223 and increased intimal hyperplasia. It has been reported that the levels of miRNAs in platelets are altered under pathological conditions, such as in DM (24,25). Assessment of both human and mouse DM platelets demonstrated consistent reductions in miR-223 expression ( Figure 5A).…”
Section: Klf4 Klf5 and Pdgfrβ Are The Critical Targets Of Mir-143 supporting
confidence: 51%
See 1 more Smart Citation
“…DM mice have reduced miR-223 and increased intimal hyperplasia. It has been reported that the levels of miRNAs in platelets are altered under pathological conditions, such as in DM (24,25). Assessment of both human and mouse DM platelets demonstrated consistent reductions in miR-223 expression ( Figure 5A).…”
Section: Klf4 Klf5 and Pdgfrβ Are The Critical Targets Of Mir-143 supporting
confidence: 51%
“…We identified a number of miRNAs that were differ entially expressed in VSMCs when cocultured with APs, including key miRNAs with established roles in regulating VSMC pheno type, such as miR-223, as well as the VSMC master miRNA cluster miR-143/145. These changes were independently validated by quantitative PCR (qPCR) at various time points (2,4,8,24, and 48 hours) following coculture with APs. We found significant upreg ulation of miRNA expression in the AP compared with the control group, with expression peaking at 4 hours for miR-223 or 24 hours for miR-143/145 ( Figure 2B).…”
Section: Introductionmentioning
confidence: 99%
“…MiR-223 is known to target P2Y 12 mRNA and lower levels may therefore convey increased resistance to P2Y 12 inhibition. Reduced expression of miR-223 in platelets has also been shown in diabetes; which is a strong risk factor for coronary artery disease and can be associated with high on-treatment platelet reactivity [34,35].…”
Section: Discussionmentioning
confidence: 95%
“…The dynamic property of platelet RNA to rapidly respond to external stimuli provides the opportunity to potentially identify surrogate RNA biomarker signatures to detect diseases such as CVD, cancer, and other diseases [9,37,46,69,[91][92][93][94][95]98]. The platelet RNA repertoire contains distinct spliced mRNA signatures for different tumor types located in different organs, allowing for tumor type-specific classification of patients with cancer using tumor-educated platelet RNA profiles [37].…”
Section: Discussionmentioning
confidence: 99%